THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND BRAND IMAGE ON ELECTRIC CAR PURCHASING DECISIONS IN PEKANBARU CITY - Trinando, Fadhil Zaky; Afwa, Awliya (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study aims to analyze the influence of product quality, price, and brand image on electric car purchasing decisions in Pekanbaru City. The increasingly rapid growth of electric vehicles indicates a shift in consumer preferences toward environmentally friendly products, but electric car purchasing decisions are still influenced by various internal and external factors. This study used a quantitative approach by distributing questionnaires to 100 respondents who had purchased electric cars. The analysis techniques used included validity and reliability tests, classical assumptions, and multiple linear regression. The results showed that product quality, price, and brand image each had a positive and significant influence on purchasing decisions. Simultaneously, all three variables were also proven to have a significant influence on consumer purchasing decisions. These findings confirm that consumer decisions in purchasing electric cars are influenced by their perceptions of product performance, the suitability of price to benefits, and brand reputation. This study has implications for automotive companies to improve quality, adjust pricing strategies, and strengthen brand image to encourage market penetration of electric cars in Indonesia